Lessons learned from a practice-based, multi-site intervention study with nurse participants - Friese, Christopher R. (J Nurs Scholarsh, 2017)
PURPOSE: To identify challenges and solutions to the efficient conduct of a multi-site, practice-based randomized controlled trial to improve nurses’ adherence to personal protective equipment use in ambulatory oncology settings. DESIGN: The Drug Exposure Feedback and Education for Nurses’ Safety (DEFENS) study is a clustered, randomized, controlled trial. Participating sites are randomized to web-based feedback on hazardous drug exposures in the sites plus tailored messages to address barriers versus a control intervention of a web-based continuing education video. APPROACH: The study principal investigator, the study coordinator, and two site leaders identified challenges to study implementation and potential solutions, plus potential methods to prevent logistical challenges in future studies. FINDINGS: Noteworthy challenges included variation in human subjects protection policies, grants and contracts budgeting, infrastructure for nursing-led research, and information technology variation. Successful strategies included scheduled web conferences, site-based study champions, site visits by the principal investigator, and centrally-based document preparation. Strategies to improve efficiency in future studies include early and continued engagement with contract personnel in sites, and proposed changes to the common rule concerning human subjects. The DEFENS study successfully recruited 393 nurses across 12 sites. To date, 369 have completed surveys and 174 nurses have viewed educational materials. CONCLUSIONS: Multi-site studies of nursing personnel are rare and challenging to existing infrastructure. These barriers can be overcome with strong engagement and planning. CLINICAL RELEVANCE: Leadership engagement, onsite staff support, and continuous communication can facilitate successful recruitment to a workplace-based randomized, controlled behavioral trial.